miR‑203a‑3p.1 is involved in the regulation of osteogenic differentiation by directly targeting Smad9 in MM‑MSCs - Fan, Fang‑Yi; Deng, Rui; Qiu, Ling; Wen, Qin; Zeng, Yunjing; Gao, Li; Zhang, Chen; Kong, Peiyan; Zhong, Jiangfan; Zeng, Ningyu; Li, Zhengyu; Su, Yi; et al. (Oncology letters, 2019)
MicroRNAs (miRNAs) have emerged as important regulators of bone development and regeneration. The aim of the present study was to determine whether miR-203a-3p.1 is involved in osteogenic differentiation of multiple myeloma (MM)-mesenchymal stem cells (MSCs) and the potential underlying mechanism. MSCs were isolated from patients with MM and normal subjects and confirmed by flow cytometry using specific surface markers. The osteogenic differentiation capacity of MM-MSCs was identified by Alizarin Red S calcium deposition staining and reverse transcription-quantitative PCR (RT-qPCR) of typical osteoblast differentiation markers. The role of miR-203a-3p.1 in the osteoblast differentiation of MM-MSCs was determined by gain or loss of function experiments. The target of miR-203a-3p.1 was identified using bioinformatics (including the miRNA target prediction database TargetScan, miRDB, DIANA TOOLS and venny 2.1.0), luciferase reporter assay, RT-qPCR and western blotting. The expression levels of proteins involved in the Wnt3a/β-catenin signaling pathway were detected by western blot analysis. The results revealed that the osteogenic differentiation capacity of MM-MSCs was reduced when compared with normal (N)-MSCs, as demonstrated by a decrease in calcium deposition and mRNA expression of typical osteoblast differentiation markers, including ALP, OPN and OC. In addition, miR-203a-3p.1 was downregulated in N-MSCs following osteoblast induction, whereas no changes were observed in MM-MSCs. The downregulation of miR-203a-3p.1 resulted in increased osteogenic potential, as indicated by the increase in the mRNA expression levels of the typical osteoblast differentiation markers, including alkaline phosphatase (ALP), osteopontin (OPN) and osteocalcin (OC). Bioinformatics and luciferase reporter assay analysis indicated that mothers against decapentaplegic homolog 9 (Smad9) may be a direct target of miR-203a-3p.1 in N-MSCs. The RT-qPCR and western blot assays revealed that overexpression of smad9 significantly enhanced the effect of miR-203a-3p.1 inhibitors on osteoblast markers, which indicated that miR-203a-3p.1 inhibitors may regulate the osteogenic differentiation of MM-MSCs by upregulating Smad9. In addition, the Wnt3a/β-catenin signaling pathway was activated following miR-203a-3p.1 inhibition. These results suggest that miR-203a-3p.1 may serve an important role in the osteogenic differentiation of MM-MSCs by regulating Smad9 expression.